Phase Transitions in the Kinetic Ising Model on the Temporal Directed Random Regular Graph - Marcjasz, Grzegorz; Sznajd-Weron, Katarzyna (Frontiers in Physics, 2017)
We investigate a kinetic Ising model with the Metropolis algorithm on the temporal directed random $q$-regular graph. We introduce a rewiring time $τ$ as a parameter of the model and show that there is a critical $τ=τ^*$ above which the model exhibits continuous order-disorder phase transition and below which the transition is discontinuous. We discuss our findings in a light of the very recent results obtained for a generalized kinetic Ising model on quenched and annealed networks.